The impact of regional and neighbourhood deprivation on physical health in Germany: a multilevel study - Razum Oliver; Berger Ursula; Voigtländer Sven (BMC, 2010)
Abstract Background There is increasing evidence that individual health is at least partly determined by neighbourhood and regional factors. Mechanisms, however, remain poorly understood, and evidence from Germany is scant. This study explores whether regional as well as neighbourhood deprivation are associated with physical health and to what extent this association can be explained by specific neighbourhood exposures. Methods Using 2004 data from the German Socio-Economic Panel Study (SOEP) merged with regional and neighbourhood characteristics, we fitted multilevel linear regression models with subjective physical health, as measured by the SF-12, as the dependent variable. The models include regional and neighbourhood proxies of deprivation (i.e. regional unemployment quota, average purchasing power of the street section) as well as specific neighbourhood exposures (i.e. perceived air pollution). Individual characteristics including socioeconomic status and health behaviour have been controlled for. Results This study finds a significant association between area deprivation and physical health which is independent of compositional factors and consistent across different spatial scales. Furthermore the association between neighbourhood deprivation and physical health can be partly explained by specific features of the neighbourhood environment. Among these perceived air pollution shows the strongest association with physical health (-2.4 points for very strong and -1.5 points for strong disturbance by air pollution, standard error (SE) = 0.8 and 0.4, respectively). Beta coefficients for perceived air pollution, perceived noise and the perceived distance to recreational resources do not diminish when including individual health behaviour in the models. Conclusions This study highlights the difference regional and in particular neighbourhood deprivation make to the physical health of individuals in Germany. The results support the argument that specific neighbourhood exposures serve as an intermediary step between deprivation and health. As people with a low socioeconomic status were more likely to be exposed to unfavourable neighbourhood characteristics these conditions plausibly contribute towards generating health inequalities.